Slowing rates of regional exhumation in the western Himalaya: fission track evidence from the Indus Fan. (3rd October 2019) - Zhou, Peng; Carter, Andrew; Li, Yuting; Clift, Peter D.
Abstract: We use apatite fission track ages from sediments recovered by the International Ocean Discovery Program in the Laxmi Basin, Arabian Sea, to constrain exhumation rates in the western Himalaya and Karakoram since 15.5 Ma. With the exception of a Triassic population in the youngest 0.93 Ma samples supplied from western Peninsular India, apatite fission track ages are overwhelmingly Cenozoic, largely <25 Ma, consistent with both a Himalaya–Karakoram source and rapid erosion. Comparison of the minimum cooling age of each sample with depositional age (lag time) indicates an acceleration in exhumation between 7.8 and 7.0 Ma, with lag times shortening from ∼6.0 Myr at 8.5–7.8 Ma to being within error of zero between 7.0 and 5.7 Ma. Sediment supply at 7.0–5.7 Ma was largely from the Karakoram, and to a lesser extent the Himalaya, based on U–Pb zircon ages from the same samples. This time coincides with a period of drying in the Himalayan foreland caused by weaker summer monsoons and Westerly winds. It also correlates with a shift of erosion away from the Karakoram, Kohistan and the Tethyan Himalaya towards more erosion of the Lesser and Greater Himalaya and Nanga Parbat, as shown by zircon U–Pb provenance data, and especially after 5.7 Ma based on Nd isotope data. Samples younger than 5.7 Ma have lag times of ∼4.5 Myr, similar to Holocene Indus delta sediments.